Nepal : Financial Sector Study - World Bank (Washington, DC, 2013)
Although financial institutions have proliferated, the Nepalese people have not yet reaped the potential gains of the government's efforts to liberalize and reform the financial sector. There are four main reasons for this: excessive government involvement in the sector, a weak central bank, a poor banking environment, and a lack of adequate banking services for the poor. The financial sector also faces other issues that impede its development such as a poorly functioning credit bureau, risky finance companies, a ceiling on foreign ownership, limited financial services, poor accounting standards, and limited use of information technology. In November 2000 the government issued a paper outlining its proposed financial sector reform program for the medium term, one which touches on all the major issues and provides sufficient basis for undertaking far-reaching reforms. While the government has committed to withdrawing from the sector as owner and operator, this study makes recommendations for making the government's strategy fully implementable. Recommendations center on five important principles: Withdrawing the government from ownership of financial institutions. Significantly strengthening the central bank to make it a fully professional institution. Restructuring the Asian Development Bank of Nepal and closing the Nepal Industrial Development Corporation. And creating an appropriate environment for establishing a sound financial sector.